Analysis of the Effect of Education and Training, Compensation and Organizational Commitment on Personnel Performance at Tanah Bumbu Police, South Kalimantan - Safaat Arif Nur Ihksan; Nurus Sjamsi (Sean Institute, 2023)
This study aims to analyze the Effect of Education and Training, Compensation and Organizational Commitment on the Performance of Police Personnel at Polres Tanah Bumbu, South Kalimantan. Sampling using the Yamane formula obtained the number of 84 samples as many as respondents. The research instrument through validity and reliability tests. Has fulfilled the classic assumption test which includes Normality, Heteroscedasticity and Multicollinearity. The data analysis technique uses Multiple Linear Regression analysis with the help of the SPSS computer program The conclusion is as follows: Education and Training (X1), Compensation (X2) and Organizational Commitment (X3) have a significant simultaneous and partial effect on the Performance of Police Personnel (Y) at Tanah Bumbu Police, South Kalimantan. Education and Training (X1) has a significant dominant effect on the Performance of Police Personnel (Y) at the Tanah Bumbu Police, South Kalimantan. This is evidenced by the beta value of the Education and Training variable (0.432) which is greater than the Compensation and Organizational Commitment variables